PENGARUH KURS, SUKU BUNGA SBI, LAJU INFLASI DAN HARGA EMAS TERHADAP INDEKS HARGA SAHAM PERTAMBANGAN - Basuki Setiyo Widodo; Fifi Swandari; Ali Sadikin (Universitas Lambung Mangkurat, 2020)
The capital market can be an option for choice for the community to make investing. The Stock Price Index (IHS-Indeks Harga Saham) is a performance indicator that measures changes in prices of a market to know its performance. Many factors affect IHS, such as the state of the global economy, oil and gold prices, exchange and interest rates, inflation, and economic conditions of a country.During the observation period of 2015-2018, there was an increase and decrease phenomenon in the Stock Price Index of Mining (IHSP-Indeks Harga Saham Pertambangan) on the Indonesia Stock Exchange (BEI-Bursa Efek Indonesia), followed by other macroeconomic conditions. There are gaps in the results of previous studies in assessing this condition.This study is to analyse the effect of exchange rates, interest rates, inflation rates and gold prices on IHSP. This research is hoped to be useful as input for other researchers and information and consideration in investing in mining companies. The data in this research were monthly data from 2015 to 2018. Samples taken are all mining companies listed on the Stock Exchange during the study period, namely 49 companies. The data is analysed using multiple linear regression test. The results of the F test showed that the four independent variables simultaneously have a significant effect on IHSP.The exchange rate and the gold price had a significant positive effect on IHSP. The interest rate had a significant negative effect on IHSP, while inflation had a negative and not significant effect on IHSP.